Treatment of chronic regional pain syndrome type 1 with palmitoylethanolamide and topical ketamine cream: modulation of nonneuronal cells - Keppel Hesselink JM; Kopsky DJ (Journal of Pain Research, 2013)
Jan M Keppel Hesselink,1 David J Kopsky21Institute for Neuropathic Pain, Bosch en Duin, The Netherlands; 2Institute for Neuropathic Pain, Amsterdam, The NetherlandsAbstract: Chronic regional pain syndrome (CRPS) can be intractable to treat and patients sometimes suffer for many years. Therefore, new treatment strategies are needed to alleviate symptoms in CRPS patients. This case report describes a patient suffering from intractable CRPS type 1 for 13 years. Due to her swollen painful feet and left knee she is wheelchair-bound. The combination of palmitoylethanolamide and ketamine 10% cream reduced her pain by more than 50% after 1 month of treatment, and a marked reduction in swelling and skin discoloration was noticed. Furthermore, she could walk independently again and she experienced no side effects. Thus, palmitoylethanolamide and topical ketamine could be a combination therapy option for treating CRPS patients.Keywords: palmitoylethanolamide, ketamine, cream, CRPS, endocannabinoid, sudeck, mast cells